Eficácia do extrato aquoso do Triticum vulgare no tratamento de radiodermatites geradas pelo uso da radioterapia em gatos - Andrade, Alexandre Lima de [UNESP]; Luvizotto, Maria Cecília Rui [UNESP]; Sakamoto, Silmara Sanae [UNESP]; Souza, Talita Floering Brêda [UNESP]; Fernandes, Marco Antônio Rodrigues [UNESP] (My University, 2010)
The use of ionizing radiation in the treatment of oncological diseases in veterinary medicine has grown in recent years. In general, these animals are very well tolerated by the treatment with radioactive elements; however, the harmful effects that may occur are not always able to be controlled, particularly those relating to skin burns. Then, the purpose of this study was to evaluate the effects of aqueous extract of Triticum vulgare in treat of 10 cats radiodermatitis with squamous cell carcinoma (SCC), which were treated with radiotherapy as single modality treatment. The drug was used topically and daily until complete healing of wounds. Based on the findings, it may concluded beneficial effects of the drug, because it allowed the formation of granulation tissue and epithelization of wounds with epidermal repair not exuberant, good-quality cosmetics and, considering the deleterious effects that can result from cancer treatments.
Efficacy of the aqueous extract Triticum vulgare in radiodermatitis treatment generated by the use of radiotherapy in cats
Keywords: Cats; Cutaneous burns; Radiotherapy; Triticum vulgare; Animalia; Triticum aestivum